Echocardiographic predictors of outcomes in adults with aortic stenosis. Issue 12 (5th April 2016) - Capoulade, Romain; Le Ven, Florent; Clavel, Marie-Annick; Dumesnil, Jean G; Dahou, Abdellaziz; Thébault, Christophe; Arsenault, Marie; O'Connor, Kim; Bédard, Élisabeth; Beaudoin, Jonathan; Sénéchal, Mario; Bernier, Mathieu; et al.
Abstract : Objective: The study purpose was to assess the usefulness of echocardiographic parameters of aortic stenosis (AS) severity and left ventricular (LV) systolic function to predict mortality in AS. The main hypothesis is that parameters of LV systolic function are the most important independent predictors of mortality, whereas parameters of stenosis severity are not. Methods: 1065 consecutive patients with AS referred to the echocardiography laboratory and meeting the inclusion/exclusion criteria were included and followed during 5.7 years. The end points were aortic valve replacement (AVR) (n=584), composite of AVR or death (n=932), all-cause mortality (n=550) and cardiovascular mortality (n=398). Results: The most powerful echocardiographic predictors of valve-related events were parameters of AS severity, such as peak aortic jet velocity (VPeak ), mean gradient (MG) and aortic valve area (AVA) (all p<0.001). Regarding mortality, the main predictors were LV ejection fraction (LVEF) and stroke volume index (SVi) (p<0.05). After multivariable adjustment, LVEF (p<0.001) and SVi (p=0.02) remained the only echocardiographic predictors of mortality, even after adjustment for symptomatic status. AVA was also associated with mortality, whereas VPeak and MG were not. Conclusions: The most powerful echocardiographic predictors of mortality are low LVEF and low flow, whereas AS severity parameters predict valve-related events but not overall mortality. Hence, low flow should be integrated in the risk stratification and therapeutic decision-making in patients with AS.